2017
DOI: 10.1007/s10384-017-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anterior chamber parameters with spectral-domain optical coherence tomography

Abstract: This study assessed anterior chamber parameters in healthy young adults using spectral-domain optical coherence tomography. This technique reveals the spatial relationships of the ocular structures, provides high-resolution images, and results in high degrees of intraobserver and interobserver repeatabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Regarding the correlation between age and angle values, our study suggested a strong negative correlation between age and angle values; that is, older age is associated with smaller angle parameters. The lens thickness increases with aging might explain this negative correlation, and several studies strongly agree with this correlation [11,12,23]. The study also indicated a strong and positive correlation between the grade of the angle (based on Shaffer classification) and angle values, and a higher angle grade (wider angle) was associated with larger angle values.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Regarding the correlation between age and angle values, our study suggested a strong negative correlation between age and angle values; that is, older age is associated with smaller angle parameters. The lens thickness increases with aging might explain this negative correlation, and several studies strongly agree with this correlation [11,12,23]. The study also indicated a strong and positive correlation between the grade of the angle (based on Shaffer classification) and angle values, and a higher angle grade (wider angle) was associated with larger angle values.…”
Section: Discussionsupporting
confidence: 60%
“…AS-OCT usage in angle-closure subjects to examine angle requires comprehensive angle biometry assessment through accurate credentials of the scleral spur as the sclera point of the inward protrusion [21]. In our study, we analyzed the AOD500, AOD750, TISA500, and TISA750 from temporal and nasal angles (from 0 to 180 degrees), which were found to be adequate for assessing the angle by many studies [10,12,17]. However, other studies included ICA measurement from superior and inferior quadrants, which might be susceptible to measurement errors due to the need for eyelid manipulation [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29 ] WTW distance, spur to spur distance, lens thickness, vault, ACA500, and AOD500 were measured using AS-OCT. ACA500 was measured by placing the apex in the iris recess, and passing the angle’s arms through a point on the trabecular meshwork at 500 μm from the point on the iris that is directly opposite to the scleral spur. [ 23 , 30 ] The AOD500 is the distance from the posterior cornea surface and the anterior iris surface, which is measured on a line perpendicular to the trabecular meshwork 500 μm from the scleral spur. [ 23 , 30 , 31 ] The measures of ACA500 and AOD500 are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…[ 23 , 30 ] The AOD500 is the distance from the posterior cornea surface and the anterior iris surface, which is measured on a line perpendicular to the trabecular meshwork 500 μm from the scleral spur. [ 23 , 30 , 31 ] The measures of ACA500 and AOD500 are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%